Spontaneous pneumopericardium an unusual complication in a patient of HIV and pulmonary tuberculosis - Chopra, Vishal (Medknow Publications & Media Pvt Ltd, 2013)
Pneumopericardium is defined as a collection of air or gas in the pericardial cavity. It is a rare entity and spontaneous pneumopericardium is even rarer. It is a rare complication of tuberculosis and human immunodeficiency virus and just three cases have been reported so far.